TS-PAID: A Two-Stage PUF-Based Lightweight Authentication Protocol for Internet of Drones - Shehzad Ashraf Chaudhry; Azeem Irshad; Bander A. Alzahrani; Ahmad Alhindi; Mohd Shariq; Ashok Kumar Das (IEEE Access)
The proliferation of Internet of Drones (IoDs)-based use cases has greatly transformed the cyberspace into pervasive and ubiquitous world. The IoD applications could range beyond military, civilian and industrial domains. However, these drones work in hostile environment, and face many challenges related to communication security. Owing to energy, storage and computational resource-constraints, the complex and heavy cryptographic solutions could not be directly deployed in IoD environment. Several authentication protocols for IoD system can be witnessed however with limitations. In this work, we have demonstrated a two-stage PUF-enabled lightweight authentication protocol (TS-PAID) for IoD setting. In comparison with related protocols, the TS-PAID bring more computational and communicational efficiencies along with resilience against known security threats including physical capture of drone. The security properties of TS-PAID are proven under formal analysis based on Real-or-Random (RoR) random oracle model. The performance findings exhibit practicality and effectiveness for the proposed scheme against the comparative studies.